Human Herpesvirus 6 (HHV-6) in the Cerebrospinal Fluid of a Newborn: Active Infection or Chromosomal Integration? - Visy, Diane; Vuckovic, Aline; Jourdain, Sarah; Smeesters, Pierre; Mignon, Céline (Belgian Journal of Paediatrics, 2025)
This article describes a case of congenital human herpesvirus-6 (HHV-6) infection in a five-day-old infant initially suspected of having meningoencephalitis. Despite positive detection of HHV-6 in cerebrospinal fluid, subsequent evaluation suggested vertical transmission of integrated virus rather than acute infection. High viral loads in cerebral spinal fluid, maternal blood, and neonatal blood supported this hypothesis. Normal neurodevelopmental evaluations during the first year of life further supported the suspicion of integrated HHV-6. This case highlights the importance of differentiating active HHV-6 infection from integrated virus and advocates whole blood quantitative PCR testing to avoid unnecessary antiviral treatment in immunocompetent infants.